Suicide attempts and death among heroin-involved women seeking methadone treatment in Taiwan. (1st December 2020) - Chen, Wan-Ting; Wang, Sheng-Chang; Wang, I-An; Tsay, Jen-Huoy; Chen, Chuan-Yu
Highlights: The risk of treated suicide attempt peaked at the end of 8th month of treatment. The risk of confirmed suicide death was stable over the first one year and a half. Depressive disorders appear to be the strongest risk factor for suicide behaviors. MMT retention may significantly lower the hazard of probable suicide death. Abstract: Background: The present study aims to profile the hazard fluctuation of suicide attempts and deaths among heroin-involved women seeking methadone maintenance treatment (MMT) and to investigate sociodemographic and clinical factors predicting the time to have suicidal behaviors. Methods: We identified a retrospective cohort comprising 2780 women receiving methadone treatment in the period of 2012–2016. Healthcare records were obtained from Taiwan's National Health Insurance Research Database, and suicide deaths were ascertained from the national death register. Competing risk survival analyses were used to estimate the risk of suicide attempts and deaths within one year and three years of MMT enrollment. Results: A total of 1.2 % of MMT-treated women ever visited hospital for suicide attempt, and 0.5 % died by confirmed suicide. The risk of treated suicide attempt reached its peak at the end of the 8th month after methadone initiation, whereas the risk of confirmed suicide death was relatively stable during the first one and a half years. A history of treated depressive disorders appears to be the strongest risk predictor for treated suicide attempts (Adjusted Hazard Ratio [aHR] = 3.45; 95 % CI = 1.66–7.19) and confirmed suicide death (aHR = 3.47; 95 % CI = 1.20–10.0). Retaining in methadone treatment may significantly lower the hazard of probable suicide death by 52 %. Conclusions: Women with heroin use disorders should receive careful attention for suicide risk at intake assessment and over the course of treatment and recovery. Preventive strategies should target unmet clinical and social needs and evaluate gender-specific barriers for treatment engagement.